The Immediate Effects of Intermittent Theta Burst Stimulation of the Cerebellar Vermis on Cerebral Cortical Excitability During a Balance Task in Healthy Individuals: A Pilot Study - Tan, Hui-Xin; Wei, Qing-Chuan; Chen, Yi; Xie, Yun-Juan; Guo, Qi-Fan; He, Lin; Gao, Qiang (Frontiers in Human Neuroscience, 2021)
Objective: This pilot study aimed to investigate the immediate effects of single-session intermittent theta-burst stimulation (iTBS) on the cerebellar vermis during a balance task, which could unveil the changes of cerebral cortical excitability in healthy individuals. Subjects: A total of seven right-handed healthy subjects (26.86 ± 5.30 years) were included in this study. Interventions: Each subject received single-session iTBS on cerebellar vermis in a sitting position. Main Measures: Before and after the intervention, all subjects were asked to repeat the balance task of standing on the left leg three times. Each task consisted of 15 s of standing and 20 s of resting. Real-time changes in cerebral cortex oxygen concentrations were monitored with functional near-infrared spectroscopy (fNIRS). During the task, changes in blood oxygen concentration were recorded and converted into the mean HbO2 for statistical analysis. Results: After stimulation, the mean HbO2 in the left SMA (P = 0.029) and right SMA (P = 0.043) significantly increased compared with baseline. However, no significant changes of mean HbO2 were found in the bilateral dorsolateral prefrontal lobe (P > 0.05). Conclusion: Single-session iTBS on the cerebellar vermis in healthy adults can increase the excitability of the cerebral cortex in the bilateral supplementary motor areas during balance tasks. Clinical Trial Registration: [www.ClinicalTrials.gov], identifier [ChiCTR2100048915].